2023
DOI: 10.3389/fonc.2023.1255555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors leading to poor outcomes for pediatric acute lymphoblastic leukemia in Mexico: a multi-institutional report of 2,116 patients

Daniel C. Moreira,
Oscar González-Ramella,
Maite Echavarría Valenzuela
et al.

Abstract: Background and aimsPediatric acute lymphoblastic leukemia (ALL) survival rates in low- and middle-income countries are lower due to deficiencies in multilevel factors, including access to timely diagnosis, risk-stratified therapy, and comprehensive supportive care. This retrospective study aimed to analyze outcomes for pediatric ALL at 16 centers in Mexico.MethodsPatients <18 years of age with newly diagnosed B- and T-cell ALL treated between January 2011 and December 2019 were included. Clinical and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Situational analyses conducted prior to launching the Bridge Project showed that while the access to diagnostic confirmation by immunophenotype was high (97%), access to specialized studies was limited; up to a third of patients with confirmed ALL lacked access to karyotype, DNA index, and MRD evaluation, and up to two-thirds of patients lacked access to FISH and PCR studies ( 18 , 19 ). These and other findings identified during situational analyses, were recently confirmed and more thoroughly evaluated in an expanded cohort, including 2,116 patients <18 years of age diagnosed at sixteen Mexican institutions between 2011-2019 ( 34 ).…”
Section: Discussionsupporting
confidence: 62%
“…Situational analyses conducted prior to launching the Bridge Project showed that while the access to diagnostic confirmation by immunophenotype was high (97%), access to specialized studies was limited; up to a third of patients with confirmed ALL lacked access to karyotype, DNA index, and MRD evaluation, and up to two-thirds of patients lacked access to FISH and PCR studies ( 18 , 19 ). These and other findings identified during situational analyses, were recently confirmed and more thoroughly evaluated in an expanded cohort, including 2,116 patients <18 years of age diagnosed at sixteen Mexican institutions between 2011-2019 ( 34 ).…”
Section: Discussionsupporting
confidence: 62%